Technology, education, life and non-life insurance in Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
This article examines the relevance of information and communication technology (ICT) in modulating the effect of education on life insurance and non-life insurance consumption in 48 African countries for the period 2004-2014. Education is measured with primary school, secondary school and tertiary school enrollments. ICT is measured with mobile phone, internet and broadband subscriptions. The empirical evidence is based on generalized method of moments. The following main findings are established. First, from the nexuses between education, ICT and life insurance, there are positive conditional effects from the interaction between: (i) broadband subscriptions and primary school enrollment; (ii) broadband subscriptions and secondary school enrollment and (iii) internet penetration and tertiary school enrollment. Second, from the nexuses between education, ICT and non-life insurance: (i) there is a negative net effect from the interactions between mobile phone penetration and primary education while positive net effects are apparent from the interactions between: mobile phone penetration and secondary school enrollment; secondary school enrollment and broadband subscriptions and; tertiary school enrollment and broadband subscriptions.
Keywords: I28; I20; I30; O16; O55; 330; Education; Technology; Insurance